Palonosetron and hydroxyzine pre-treatment reduces the objective signs of experimentally-induced acute opioid withdrawal in humans: a double-blinded, randomized, placebo-controlled crossover study. (2nd January 2017) - Erlendson, Matthew J.; D'Arcy, Nicole; Encisco, Ellen M.; Yu, Jeffrey J.; Rincon-Cruz, Lorena; Peltz, Gary; Clark, J. David; Chu, Larry F.
ABSTRACT: Background : Treatments for reducing opioid withdrawal are limited and prone to problematic side effects. Laboratory studies, clinical observations, and limited human trial data suggest 5-HT3-receptor antagonists and antihistamines may be effective. Objectives : This double-blind, crossover, placebo-controlled study employing an acute physical dependence model evaluated whether (i) treatment with a 5-HT3-receptor antagonist (palonosetron) would reduce opioid withdrawal symptoms, and (ii) co-administration of an antihistamine (hydroxyzine) would enhance any treatment effect. Methods : At timepoint T = 0, healthy (non-opioid dependent, non-substance abuser) male volunteers ( N = 10) were pre-treated with either a) placebo, b) palonosetron IV (0.75 mg), or c) palonosetron IV (0.75 mg) and hydroxyzine PO (100 mg) in a crossover study design. This was followed at T = 30 by intravenous morphine (10 mg/70kg). At T = 165, 10 mg/70kg naloxone IV was given to precipitate opioid withdrawal. The objective opioid withdrawal score (OOWS) and subjective opioid withdrawal score (SOWS) were determined 5 and 15 minutes after naloxone administration ( T = 170, 180, respectively). Baseline measurements were recorded at T = −30 and T = −15. Results : Comparison of average baseline OOWS scores with OOWS scores obtained 15 minutes after naloxone was significant ( p = 0.0001). Scores from 15 minutes post-naloxone infusion showed significant differences in OOWS scores between treatment groups: placebo, 3.7 ± 2.4; palonosetron, 1.5 ± 0.97; and palonosetron with hydroxyzine, 0.2 ± 0.1333. Conclusions : Pretreatment with palonosetron significantly reduced many signs of experimentally-induced opioid withdrawal. Co-administration with hydroxyzine further reduced opioid withdrawal severity. These results suggest that 5-HT3 receptor antagonists, alone or in combination with an antihistamine, may be useful in the treatment of opioid withdrawal.